1980
DOI: 10.1093/geronj/35.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Conservatism: Cohort Changes in Attitudes About Legalized Abortion

Abstract: Cohort changes in attitudes about the availability of legal abortions are traced over a twelve year period using data from seven national surveys. Contrary to the aging-conservatism hypothesis, trends in the direction of increasingly favorable attitudes between 1965 and 1973 and general stability thereafter characterize all cohorts. On this issue, there is no evidence of growing conservatism, attitudinal rigidity, or change at a slower rate among the older cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, the data would not appear to fit that model given the absence of pronounced differential rates of change. The model that appears to be most consistent with these data, as well as earlier findings on attitudes about race relations 19 and support for the legalisation of abortion, 18 is one which suggests that the social and cultural forces influencing attitudes (and changes therein) have been uniform across cohorts. Such a 'constant' or 'period' effect model would lead us to expect change in the same direction and to the same extent among all cohorts when public opinion at large is moving in a liberal (or conservative) direction.…”
Section: Summary and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the data would not appear to fit that model given the absence of pronounced differential rates of change. The model that appears to be most consistent with these data, as well as earlier findings on attitudes about race relations 19 and support for the legalisation of abortion, 18 is one which suggests that the social and cultural forces influencing attitudes (and changes therein) have been uniform across cohorts. Such a 'constant' or 'period' effect model would lead us to expect change in the same direction and to the same extent among all cohorts when public opinion at large is moving in a liberal (or conservative) direction.…”
Section: Summary and Discussionsupporting
confidence: 74%
“…Yet, the results of still other studies raise doubts about the universality of the ageing-stability model as a description of attitude change. In one analysis, Cutler et al 18 examined intra-cohort changes in attitudes about the legalisation of abortion over the period [1965][1966][1967][1968][1969][1970][1971][1972][1973][1974][1975][1976][1977]. The findings from this study show that reported support for legalised abortion increased at approximately the same rate for all cohorts.…”
Section: Introductionmentioning
confidence: 98%
“…As Cutler et al. () note, there are “psychologically‐based, age‐related changes in the direction of greater rigidity, cautiousness, and growing resistance to change, all of which leads to ‘a greater stake in the maintenance of the status quo’” (Cutler et al. :115).…”
Section: Why This Cohort?mentioning
confidence: 99%
“…() note, there are “psychologically‐based, age‐related changes in the direction of greater rigidity, cautiousness, and growing resistance to change, all of which leads to ‘a greater stake in the maintenance of the status quo’” (Cutler et al. :115). As a result, as the respondents move through the lifecycle, I would expect that the coefficients would become negatively signed and significantly different from zero.…”
Section: Why This Cohort?mentioning
confidence: 99%
“…The comparisons are organised in terms of a design suggested by Palmore (1978) for separating age, historical period and cohort effects. A nice illustration of this methodology can be found in Cutler, Lentz, Muha, and Riter (1980). This design uses at least three groups separated by a fixed number of years (here 15 years) (see Figure 1).…”
Section: Testing Level Stability Of the Five Sets Of Beliefsmentioning
confidence: 99%